PENGEMBANGAN CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL TRADISI TOLAK BALA ALA SUKU DAYAK UNTUK SISWA SEKOLAH DASAR - Margareth Febi Patrizki Dami; Susanto, Moh. Rusnoto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Local wisdom has been included in the 2013 elementary school curriculum thematic learning. Based on interviews conducted by researchers with fifth grade teachers at Muhammadiyah Tamantirto Elementary School, researchers received information that currently teachers are getting students used to creating stories and literacy materials in the library still do not provide many visuals about culturally based picture stories. Therefore, researchers developed the video